PENGELOLAAN TANAH WAKAF SEBAGAI SARANA PEMBERDAYAAN MASYARAKAT - Musthofa Musthofa (LPPM IAI IBRAHIMY GENTENG BANYUWANGI, 2019)
Legal development aims to establish and secure the implementation of development and its results. The effort that needs to be done to achieve that goal is by reforming the law in a directed and integrated manner and supporting development in various fields as well as legal awareness and dynamics that develop in the ummah. One of the efforts towards the development of law, among others relating to; First, Land, which has been regulated in PP. No. 28/1977 concerning the representation of property as the implementing regulation of article 49 paragraph 3 of the Law. No 5/1960 Basic Principles of Agrarian Affairs. Second, the law (Islamic jurisprudence). Land